PDF Biosensing technique for detection of H.pylori bacteria: Israa M.L. SaQari*, Layla M.H. Al-ameri - M.L. SaQari, Israa (Iraqi Journal of Laser, 2022)
Abstract :H.pylori is an important cause of gastric duodenal disease, including gastric ulcers, Mucosa-associated lymphoid tissue (MALT), and gastric carcinoma. biosensors are becoming the most extensively studied discipline because the easy, rapid, low-cost, highly sensitive, and highly selective biosensors contribute to advances in next-generation medicines such as individualized medicine and ultrasensitive point-of-care detection of markers for diseases. Five of ten patients diagnosed with H.pylori ranging in age from 15–85 participated in this research. who [gastritis, duodenitis, duodenal ulcer (DU), and peptic ulcer (PU)] Suspected H.pylori colonies were identified by the presence of urease, catalase, oxidase activity, and PCR. All parameters are fixed: Laser power:40 mW, size of drops:25 μ, Turbidity:0.5. , Multi modes optical fiber, and Coreless optical fiber to construct optical biosensor (Multimode-Coreless-Multimode) optical fibers based on an inline Mach-Zehnder Interferometer. All samples had a sensitivity. Multimode-Coreless-Multimode optical Biosensor: is a rapid and sensitive method for the detection of H.pylori bacteria.